2019
DOI: 10.3389/fendo.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Feeding and Metabolism by Neuropeptide F and Short Neuropeptide F in Invertebrates

Abstract: Numerous neuropeptide systems have been implicated to coordinately control energy homeostasis, both centrally and peripherally. However, the vertebrate neuropeptide Y (NPY) system has emerged as the best described one regarding this biological process. The protostomian ortholog of NPY is neuropeptide F, characterized by an RXRF(Y)amide carboxyterminal motif. A second neuropeptide system is short NPF, characterized by an M/T/L/FRF(W)amide carboxyterminal motif. Although both short and long NPF neuropeptide syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 196 publications
(235 reference statements)
3
123
0
Order By: Relevance
“…Thus, N. lugens is a promising insect model for the in-depth exploration of magnetoreception mechanisms. In addition to the potential magnetoreceptor Crys and multifunctional AKH-AKHR signaling, here we also explored the expression of orexigenic neuropeptide F (NPF) and short NPF (sNPF) genes thought to play a role in appetite regulation (Fadda et al, 2019;Lin et al, 2019). Combining the investigation of magnetic field effects on feeding behavior along with glucose levels suggested to be negatively correlated with appetite (Timper and Bruning, 2017;Ugrankar et al, 2018), and the expression of appetite-related genes, we provide the first evidence that reducing GMF intensity negatively affects energy homeostasis in animals by altering feeding behavior and its underlying regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, N. lugens is a promising insect model for the in-depth exploration of magnetoreception mechanisms. In addition to the potential magnetoreceptor Crys and multifunctional AKH-AKHR signaling, here we also explored the expression of orexigenic neuropeptide F (NPF) and short NPF (sNPF) genes thought to play a role in appetite regulation (Fadda et al, 2019;Lin et al, 2019). Combining the investigation of magnetic field effects on feeding behavior along with glucose levels suggested to be negatively correlated with appetite (Timper and Bruning, 2017;Ugrankar et al, 2018), and the expression of appetite-related genes, we provide the first evidence that reducing GMF intensity negatively affects energy homeostasis in animals by altering feeding behavior and its underlying regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The role of NPY in the regulation of feeding and satiety has been explored in both protostome and deuterostome taxa since the 1990s (Hanson et al, 1995). One extensively conserved role for NPY is as an orexigenic (appetite-stimulating) factor (Beck, 2006, Christie et al, 2011, Di Cristo et al, 2017, Fadda et al, 2019.…”
mentioning
confidence: 99%
“…It is noteworthy that NPY/NPF-type signalling has only 621 been partially characterised in a model invertebrate system -the nematode C. elegans. Our 622 phylogenetic analysis indicates that there are two C. elegans receptors that are orthologs of 623 NPY/NPF-type receptors: NPR-12, which is an orphan receptor, and NPR-11, which has 624 been shown to be activated by the peptide MDANAFRMSFamide based on similarity-based sequence alignments, it has been suggested that the mature peptide 631 derived from the C. elegans protein FLP-27 may be an ortholog of NPY/NPF-type peptides 632 (Fadda et al 2019). Here, our analysis of the structure of the gene encoding the FLP-27 633 precursor has revealed that it has the characteristic structure of NPY/NPF-type genes, with an 634 intron interrupting the codon for the C-terminal arginine of the NPF-type peptide sequence.…”
mentioning
confidence: 99%
“…Thus, the determination of deep homology 808 relationships is normally accomplished by generating phylogenetic trees (Gabaldón 2008). 809 Nevertheless, informed by the hypothesis of Jekely (2013) that sNPF-type signalling may 810 be orthologous to PrRP-type signalling, which was also reported in a recent review article 811 (Fadda et al, 2019), here we investigated the occurrence PrRP-like neuropeptides in the 812 hemichordate S. kowalevskii and the cephalochordate B. floridae. Importantly, we identified 813 one precursor protein in B. floridae and two precursor proteins in S. kowalevskii that contain 814 peptides that share sequence similarity with both echinoderm sNPF-type neuropeptides and 815 with vertebrate PrRP-type neuropeptides.…”
mentioning
confidence: 99%